The Relationship Between Organizational Justice and Social Loafing in Ho Chi Minh City-based Enterprises - Thanh, Vu Ba; Toan, Ngo Van (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 33 No 4, 2017)
Social loafing is the phenomenon of a person exerting less effort to achieve a goal when they work in a group than when they work alone, and it is influenced by organizational justice. This study investigates the relationship between organizational justice and social loafing in Ho Chi Minh City - based enterprises through quantitative analysis. The result show that only distribution justice and procedural justice produce an opposite effect on employee’s social loafing. Keywords Organizational justice, social loafing, enterprise References [1] Latané, B., Williams, K., & Harkins, S. (1979). Many hands make light the work: The causes and consequences of social loafing. Journal of personality and social psychology, 37(6), 822-832. [2] George, J. M. (1992). Extrinsic and intrinsic origins of perceived social loafing in organizations. Academy of Management Journal, 35(1), 191-202. [3] Etemadi, M., Darab, M. G., Khorasani, E., Moradi, F., & Vazirinasab, H. (2015). Social loafing among nurses and its relation with organizational justice. International Journal of Educational and Psychological Researches, 1(2), 125. [4] Bennett, N., & Naumann, S. E. (2005). Understanding and Preventing Shirking, Job Neglect, Social Loafing, and Free Riding. Managing organizational deviance, 113-129.Karau, S. J., & Williams, K. D. (1993). Social loafing: A meta-analytic review and theoretical integration. [5] Aggarwal, P., & O'Brien, C. L. (2008). Social loafing on group projects: Structural antecedents and effect on student satisfaction. Journal of Marketing Education, 30(3), 255-264. [6] Murphy, S. M., Wayne, S. J., Liden, R. C., & Erdogan, B. (2003). Understanding social loafing: The role of justice perceptions and exchange relationships. Human relations, 56(1), 61-84. [7] Mortazavi, S., Hakimi, H., Soori, N., & Gholizade, R. (2011). Investigation of perception of justice and trust on teams social loafing in knowledge sharing: Research and development teams in Mashhad Industrial Town. Exec Manage Bull, 3, 137-62. [8] Liden, R. C., Wayne, S. J., Jaworski, R. A., & Bennett, N. (2004). Social loafing: A field investigation. Journal of Management, 30(2), 285-304. [9] Lin, T. C., & Huang, C. C. (2009). Understanding social loafing in knowledge contribution from the perspectives of justice and trust. Expert Systems with Applications, 36(3), 6156-6163. [10] Greenberg J. (1990), “Looking Fair Being Fair: Managing Impressions of Organizational Justice”, Research in Organizational Behavior, 12(1), pp. 57-111. [11] Bies, R. J. (2001). Interactional (injustice: The sacred and the profane. In J. Greenberg & R. Cropanzano (Eds.), Advances in organizational justice (pp. 89-118). [12] Lipponen, J., Olkkonen, M. E., & Myyry, L. (2004). Personal value orientation as a moderator in the relationships between perceived organizational justice and its hypothesized consequences. Social Justice Research, 17(3), 275-292. [13] Simms, A., & Nichols, T. (2014). Social loafing: a review of the literature. Journal of Management Policy and Practice, 15(1), 58. [14] Ingham, A. G., Levinger, G., Graves, J., & Peckham, V. (1974). The Ringelmann effect: Studies of group size and group performance. Journal of Experimental Social Psychology, 10(4), 371-384. [15] Williams, K., Harkins, S. G., & Latané, B. (1981). Identifiability as a deterrant to social loafing: Two cheering experiments. Journal of Personality and Social Psychology, 40(2), 303. [16] Ferrante, C. J., Green, S. G., & Forster, W. R. (2006). Getting more out of team projects: Incentivizing leadership to enhance performance. Journal of Management Education, 30(6), 788-797. [17] Kaneshiro, P. (2008). Analyzing the organizational justice, trust, and commitment relationship in a public organization (Doctoral dissertation, [Sl: sn]).